2022
DOI: 10.1038/s41396-022-01264-1
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting biocrystallization: purine crystalline inclusions are widespread in eukaryotes

Abstract: Despite the widespread occurrence of intracellular crystalline inclusions in unicellular eukaryotes, scant attention has been paid to their composition, functions, and evolutionary origins. Using Raman microscopy, we examined >200 species from all major eukaryotic supergroups. We detected cellular crystalline inclusions in 77% species out of which 80% is composed of purines, such as anhydrous guanine (62%), guanine monohydrate (2%), uric acid (12%) and xanthine (4%). Our findings shifts the paradigm ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…In the case of eukaryotic microorganisms, although purine crystals have been known for many years, their composition has been investigated in detail in the last years [ 3 ]. In a very recent study that investigated crystalline inclusions in diverse unicellular eukaryotes, almost all guanine crystals contained anhydrous guanine with just a few examples containing the monohydrate form [ 33 ]. It is possible that detailed analysis of other bacteria could lead in the future to the discovery of other kinds of organic crystals, as already observed in eukaryotes [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the case of eukaryotic microorganisms, although purine crystals have been known for many years, their composition has been investigated in detail in the last years [ 3 ]. In a very recent study that investigated crystalline inclusions in diverse unicellular eukaryotes, almost all guanine crystals contained anhydrous guanine with just a few examples containing the monohydrate form [ 33 ]. It is possible that detailed analysis of other bacteria could lead in the future to the discovery of other kinds of organic crystals, as already observed in eukaryotes [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the in situ determination of the chemical composition of intracellular structures, a confocal Raman microscope (alpha300 RSA; WITec, Germany) was used as previously described ( 56 60 ). To immobilize the fast-moving flagellates on the quartz slide, 5 μL of the cell pellet was mixed with 5 μL of 1% (wt/vol) solution of low-melting-point agarose (catalog number 6351.5; Carl Roth, Germany), immediately spread as a single-cell layer between a quartz slide and coverslip, and sealed with CoverGrip sealant (Biotium, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of eukaryotic microorganisms, although purine crystals have been known for many years, their composition has been investigated in detail in the last years 3 . In a very recent study that investigated crystalline inclusions in diverse unicellular eukaryotes, almost all guanine crystals contained anhydrous guanine with just a few examples containing the monohydrate form 31 . Guanine crystals are associated with melanin in many organisms 2,32,33 .…”
Section: Biological and Genetic Aspects Of Guanine Crystal Synthesismentioning
confidence: 99%
“…Their occurrence in other organisms, such as unicellular eukaryotes, was studied many years ago 9,36 , and thought to be limited to a few cases. Recent renewed interest in guanine crystals and the application of new technologies has expanded this knowledge, and a very recent study showed them to be widespread among eukaryotic microorganisms 31 . Our work has demonstrated their presence in prokaryotes, extending the range of guanine crystal producing organisms to a new Domain of life.…”
Section: Biological and Genetic Aspects Of Guanine Crystal Synthesismentioning
confidence: 99%